Preventive activity of police bodies: realities and challenges in the conditions of martial law - A. O. Ivanov (Law and Safety)
The materials of the Ministry of Internal Affairs of Ukraine and the National Police of Ukraine leadership reports on the challenges and problems that the bodies of the Ministry of Internal Affairs had to face as a result of military aggression by the Russian Federation have been considered, as well as on the available results and successes in countering the threats of war by the police and implementing their normal tasks and functions under martial law. It has been emphasized that one of the main areas of the National Police of Ukraine activity was and remains preventive activity, the high efficiency and effectiveness of which are especially important in the conditions of martial law. At the same time, in such a situation, it is quite difficult to ensure the appropriate level of quality and effectiveness of the specified activity due to the objective conditions of wartime, which significantly complicate the work of the police. The key, in our opinion, factors that create difficulties and complications in the implementation of preventive activities by police bodies in conditions of martial law have been identified. In particular, these are changes in the trends and structure of illegal activity in the country; the growth of migration flows, both of an internal and external nature; increase in the number of firearms in civilian circulation; activation of social movement; the need for the police to perform a number of previously uncharacteristic tasks, etc. The author's vision of priority directions for further improvement and development of preventive activities of police bodies in the conditions of wartime and post-war reconstruction of Ukraine has been expressed.